Differential distribution shifts in two subregions of East Asian subtropical evergreen broadleaved forests—a case of Magnoliaceae - Wu, Hai-Yang; Liu, Yue-Han; He, Qiu-Xiang; Ye, Jun-Wei; Tian, Bin (Frontiers in Plant Science, 2024)
Aim East Asian subtropical evergreen broad-leaved forests (EBLFs) are composed of western and eastern subregions with different topographical and environmental conditions. The distribution shifts over time of plants in the two subregions are predicted to be different, but the difference has seldom been investigated. Methods Potential distributions of 53 Magnoliaceae species (22 in the western and 31 in the eastern subregion) during the last glacial maximum (LGM), present, and the 2070s were predicted using MaxEnt based on 58 environmental variables. The changes in the distribution range size and centroid over time were analyzed. Species-level potential habitats were overlaid to uncover species diversity distribution, and the distributions over time were overlaid to discover long-term refugia. Results At present, the potential distributions are significantly larger than those shown by the occurrence points. During the LGM, 20/22 species in the western subregion experienced increases in range size through downwards and southward migrations, while decreases in range size in the eastern subregion (27/31 species) were accompanied by northward and eastward migrations. In the future, range size declines and northward shifts will both be found; northwestward shifts will exist in most (20/22 species) species in the western subregion, while both northwest- and northeastward shifts will occur in the eastern subregion. The diversity hotspots experienced a slight southward shift in the past and upwards to the mountain region in the future in the western subregion; in the eastern subregion, shrinks occurred in eastern China in the past and shrinks were shown in all regions in the future. Long-term refugia-preserving diversity was found in the mountains across the entire EBLFs region. Main conclusions Significant differences in distribution shifts from past to present and similar distribution shifts from present to future are revealed in the two subregions. Species diversity in both subregions experienced no significant shifts from past to future, and Magnoliaceae plants could be preserved in mountainous regions throughout the EBLFs.